2018
DOI: 10.1186/s13075-018-1567-2
|View full text |Cite
|
Sign up to set email alerts
|

Failure of remission induction by glucocorticoids alone or in combination with immunosuppressive agents in IgG4-related disease: a prospective study of 215 patients

Abstract: BackgroundThe aim of this study was to assess the outcomes of remission induction in patients with IgG4-related disease (IgG4-RD) in our cohort, and to investigate the characteristics, prognosis, and risk factors in the patients failed of remission induction.MethodsWe prospectively enrolled 215 newly diagnosed patients with IgG4-RD, who were initially treated with glucocorticoid (GC) alone or in combination with immunosuppressive agents (IM), and had at least 6 months of follow up. The therapeutic goals of rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 36 publications
0
48
0
5
Order By: Relevance
“…In addition, there are some studies published in Chinese which showed iguratimod treatment was effective for primary Sjögren's syndrome and patient's serum Ig was decreased as well. As we know, one of the most prominent characteristics of IgG4‐RD is activation of B cells and plasmablast cells, which excrete large amount of serum IgG and IgG4 . Therefore, we think that iguratimod treatment may be effective in the treatment of IgG4‐RD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there are some studies published in Chinese which showed iguratimod treatment was effective for primary Sjögren's syndrome and patient's serum Ig was decreased as well. As we know, one of the most prominent characteristics of IgG4‐RD is activation of B cells and plasmablast cells, which excrete large amount of serum IgG and IgG4 . Therefore, we think that iguratimod treatment may be effective in the treatment of IgG4‐RD.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoglobulin G4‐related disease (IgG4‐RD) is a newly defined chronic fibro‐inflammatory disorder characterized by elevated serum IgG4 levels, tumefactive lesions with a dense lymphoplasmacytic infiltration rich in IgG4 positive plasma cells and storiform fibrosis of related organs . Glucocorticoids are the first‐line agents for the treatment of IgG4‐RD; however, in order to maintain long‐term disease stability and avoid disease relapse, usually glucocorticoids maintenance therapy should last for a long period, which may induce various glucocorticoid‐associated adverse reactions. For some IgG4‐RD patients with mild symptoms, such as swelling of the lacrimal glands, submandibular glands, parotid glands and nasal sinus, without internal organ damage, long‐term glucocorticoids therapy for mild symptoms may have a low benefit/risk ratio.…”
Section: Introductionmentioning
confidence: 99%
“…The initial 6-month period was defined as the remission induction stage, and the therapeutic goals of this stage were defined as fulfilling each of the following: (1) ≥ 50% decline in the IgG4-RD RI, (2) GC tapered to maintenance dose (prednisone ≤ 10 mg/day), and (3) no relapse during GC tapering (within 6 months) [16].…”
Section: Goals Of Remission Inductionmentioning
confidence: 99%
“…An increasing number of studies on the outcomes and prediction of disease relapse in IgG4-RD showed that high baseline serum IgG4, IgE, and eosinophilia could predict IgG4-RD relapse independently [15]; eosinophilia, higher baseline RI, having five or more organs involved, and dacryoadenitis were risk factors for remission induction failure with GC monotherapy [16]; and hypocomplementemia was more frequent in IgG4related kidney disease (IgG4-RKD), which may participate in the disease development [17,18]. However, the disease subclass, outcomes, and predictors of disease relapse in IgG4-RD still require further exploration.…”
mentioning
confidence: 99%
“…Recurrence rates for corticosteroid monotherapy range from 20.8% to 43%. Factors considered to be less favorable in terms of prognosis include high initial serum IgG4 levels and insufficient treatment duration [14,15]. Alternative treatment options include steroid-sparing immunosuppressants such as methotrexate, azathioprine or mycophenolate mofetil.…”
Section: Discussionmentioning
confidence: 99%